2022
DOI: 10.3389/fimmu.2022.890353
|View full text |Cite
|
Sign up to set email alerts
|

Liver Ischemia and Reperfusion Induce Periportal Expression of Necroptosis Executor pMLKL Which Is Associated With Early Allograft Dysfunction After Transplantation

Abstract: BackgroundEarly allograft dysfunction (EAD) following liver transplantation (LT) remains a major threat to the survival of liver grafts and recipients. In animal models, it is shown that hepatic ischemia-reperfusion injury (IRI) triggers phosphorylation of Mixed Lineage Kinase domain-like protein (pMLKL) inducing necroptotic cell death. However, the clinical implication of pMLKL-mediated cell death in human hepatic IRI remains largely unexplored. In this study, we aimed to investigate the expression of pMLKL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Both apoptosis and necrosis were observed in hepatocytes after IR [ 25 ]. IR induces periportal expression of MLKL in human liver grafts, and is associated with early allograft dysfunction after transplantation [ 26 ]. Ferroptosis is induced by iron overload during liver IR injury [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both apoptosis and necrosis were observed in hepatocytes after IR [ 25 ]. IR induces periportal expression of MLKL in human liver grafts, and is associated with early allograft dysfunction after transplantation [ 26 ]. Ferroptosis is induced by iron overload during liver IR injury [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of these studies are based on cell culture and animal models. There are only two human organ studies, one in the lung [ 40 ] and another in the liver [ 35 ]. More clinical research should be conducted to determine the significance of necroptosis in human organ transplants.…”
Section: Discussionmentioning
confidence: 99%
“…Human liver grafts with a high pMLKL index had significantly elevated serum levels of aminotransferases and lactate dehydrogenase 24 h after transplantation, signifying lytic cell death. Thus, the pMLKL index can serve as a reliable prognostic tool for the progression of EAD [ 35 ].…”
Section: Necroptosis In Solid Organ Transplantationmentioning
confidence: 99%
“…Overall evidence suggests that necroptosis plays a relevant role as a form of lytic cell death in the IRI model, although some studies do not attribute any effects to necroptosis [ 208 , 209 ]. A recent study revealed the presence of activated MLKL in human liver grafts before and after reperfusion [ 210 ]. Interestingly, patients experiencing early allograft dysfunction show a significant increase in MLKL activation, which correlates with serum liver enzyme levels.…”
Section: Cell Death In Liver Diseasementioning
confidence: 99%